Innate Variability in Voluntary Drinking in Arabian Horses during Endurance Exercise. (June 2014) - Butudom, P; Spooner, H; Duesterdiek‐Zellmer, K; Harris, P; Schott II, H
Abstract : Introduction: Human athletes have been characterized as either 'good drinkers' or 'poor drinkers' on the basis of voluntary water intake during and after endurance exercise. Similarly, riders of endurance horses have described some horses to be better drinkers than others; however, there are no data in horses to substantiate these claims. Methods: Voluntary fluid intake (FI) by twenty four 2‐year‐old Arabian horses that performed 45–60 km of treadmill exercise in four experiments was recorded. All horses were raised similarly and had no training except a 12 week conditioning period before each experiment. Mean FI intake (each horse performed three or four exercise tests in each experiment) was subjected to cluster analysis to separate horses into poor, average, and excellent drinking groups. FI was also correlated to body weight (BW) loss at the end of the exercise test. Results: Cluster analysis separated horses into poor drinkers (n = 10, FI 8.7 ± 0.7 liters and BW loss of 2.2 ± 0.4%); average drinkers (n = 11, FI 14.1 ± 0.6 liters and BW loss of 1.8 ± 0.2%); and excellent drinkers (n = 3, FI 24.9 ± 0.2 liters and BW loss of 0.7 ± 0.3%). FI was inversely correlated with BW loss (R values between −0.53 and −0.87 for all four experiments, P<0.01). Conclusions: These data, in groups of young, similarly trained horses, are the first to support that there are innate differences in voluntary drinking during and after endurance exercise in this species. Ethical Animal Research: All procedures were approved by the Animal Use Committee of Michigan State UniversitySources of funding: Equine Health Research Fund of the American Horse Shows Association, WALTHAM Centre for Pet Nutrition, and the Department of Large Animal Clinical Sciences, Michigan State University.Competing interests: none.